Classification of Acanthaceae - Scotland, R; Vollesen, K (2000)
The classification of Acanthaceae is discussed relative to recent molecular studies, pollen morphology, corolla aestivation and other potentially informative morphological homologues. The major pollen types of Acanthaceae are illustrated in the form of scanning electron micrographs. A three-item analysis of 11 morphological homologues is provided. A new classification of Acanthaceae is presented in addition to a list of generic synonymy.